EDI Technology for Paperless Transactions. - Abaya, Efren F.
"Electronic Data Interchange" or EDI refers to the electronic transmission of commercial documents in a standard format. The standardized characteristics of the electronic transmission will allow a business transaction to be conducted in a purely automated manner. This tutorial paper will discuss the technical concepts of EDI using as an example the UN EDIFACT standard.